Donor site morbidity following resection of vascularized free fibular graft for skeletal reconstruction - Muhd Ruzaimi, Abd Razak (2008)
Fibular graft is a useful technique to restore skeletal integrity of bony defects. Despite the benefit of this procedure, there are some reported problems associated with donor site particularly with regards to ankle joint The purpose of this study to objectively measure the morbidity to the ankle joint after fibular graft harvest and to study the significant radiological changes in ankle joint. Also to know the residual distal length of the fibula that should be maintain to minimize the donor site morbidity A cross-section study was performed on patients who had undergone autogenous vascularized fibular graft harvest. Twenty patient who had undergone unilateral fibula harvest with normal contralateral ankle were identified. Patients were evaluated within 15 to 96 months post operation with average of 45.25 month. Mazur's ankle score. was used to analyses the subjective symptom and sign. Radiological assessments to both ankle which include mortice views on non weight bearing and weight bearing were performed. The distance of the tips of lateral melleolus and the tips of medial melleolus were calculated and the tilting angle of the residual distal fibula were measured Mazur's ankle score shows 15(75%) patients has excellence outcome ( scoring mark 90 and above) and 5(15%) patients had good outcome (scoring mark from 79 to 89), none of them had fair or poor results. In weight bearing mortise view of ankle x-ray, there is significant proximal migration of residual distal fibula with average 7.45 mm. The analysis for correlation between Mazur's ankle score and residual distal length of fibula shows a significant positive linear correlation with a good correlation. Mazur's ankle score are good objective scoring system for subjective assessment of donor site following vascularized fibular grafting. Limitation of functional activity to the ipsilateral ankle following fibular harvest is not considered significant enough to discourage transplantation of large segment of fibula. There is significant radiological changes in mortise view of ankle x-ray post fibular harvest especially proximal migration of residual distal fibula on weight bearing. The significant linear correlation between Mazur's ankle score with residual distal length of fibula was observed. The minimum of 7 em residual distal fibular correlate with Mazur's ankle score more than 90%.